Epidemiology of injuries in female high school soccer players - Sentsomedi, Keamogetse Refilwe (Afr Health Sci, 2016)
BACKGROUND: Sport is a compulsory activity in schools in South Africa. Female learners participating in soccer are more vulnerable to injuries than males. OBJECTIVE: This study determined the epidemiology of injuries in female high school soccer players. METHODS: A cross sectional survey captured the epidemiology of injuries in the players. The population included 200 players from 27 high schools in one district between the ages of 14 to 19 years. A self-administered questionnaire was used to collect data. RESULTS: Only 85 scholars from 8 schools participated. From the 85 respondents, 31 (36.5%) sustained injuries. Only 61 injuries were reported by the injured players. The injury prevalence for the season was 36.5%. The rate of injury was 90 per 1000 athlete exposure hours during the season. The defenders and midfielders sustained the most injuries. Most injuries reported were contact in nature. More injuries occurred during training than during matches. The lower extremity (77.8%) was injured more than the upper extremity (22.2%). The knee (22.2%) and ankle (15.9%) were the most frequently injured body parts. Muscle injury was the most commonly reported followed by bruising. CONCLUSION: Prevalence of injuries was high with the lower limb, specifically the knee and ankle being commonly injured.